Dry Corn Corn Marketing System Moisture Content 14% in Rarampadende Village, Dolo Barat District, Sigi Regency - Endah Wahyunuing Asih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Sigi Regency's efforts in achieving the goals of improving welfare and increasing work competence of human resources, especially hybrid corn farmers in Rarampadende Village, Dolo Barat District, are through the application of the use of a moisture tester (Moisture Tester), which is a full-time activity for measuring corn moisture content. From the beginning, the average moisture content of 28-30% when harvested to 14% moisture content. How is the economic influence of farmers on the marketing of dry-shelled corn with a moisture content of 14% in Rarampadende Village, West Dolo District, Sigi Regency, and how is the economic influence in the use of the Moisture Tester on dry-shelled corn in Rarampadende Village, West Dolo District, Sigi Regency. Based on the description of the discussion above, it can be concluded that: The structure of the corn market that takes place in Central Sulawesi Province is not yet efficient, and the market structure that is formed leads to an imperfect competition market (oligopsony). And wholesalers as the dominant marketing agency in determining the price of corn. This is due to collaboration in price formation between brokers and wholesalers, one of the causes of price domination by wholesalers.